2023
DOI: 10.1007/s12325-023-02450-z
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Should Embrace Precision Medicine: Evidence by Reviewing Economic Evaluations in China

Abstract: The cost-effectiveness of conventional population-based breast cancer screening strategies (e.g. mammography) has been found controversial, while evidence shows that genetic testing for early detection of pathogenic variants is cost-effective. We aimed to review the economic evaluations of breast cancer screening in China to provide an information summary for future research on this topic. We searched the literature to identify the economic evaluations that examined breast cancer screening and testing in China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Both the incidence of BC and deaths resulting from BC continue to rise, and its associated mortality is mainly due to disease progression or metastasis ( 27 ). The lack of early-stage diagnostic techniques and effective treatment methods continues to present major problems for the administration of BC therapy worldwide ( 28 ). Moreover, ~6-10% of newly diagnosed cases of BC are identified at stage IV of the disease, or the BC is already metastatic ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the incidence of BC and deaths resulting from BC continue to rise, and its associated mortality is mainly due to disease progression or metastasis ( 27 ). The lack of early-stage diagnostic techniques and effective treatment methods continues to present major problems for the administration of BC therapy worldwide ( 28 ). Moreover, ~6-10% of newly diagnosed cases of BC are identified at stage IV of the disease, or the BC is already metastatic ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown both that PTX3 is overexpressed in various tumors, and that it is involved in cancer progression through multiple signaling pathways ( 28 , 29 ). A recently published study ( 30 ) demonstrated that the transcription factor SOX9 directly regulates the expression of PTX3, whereas human leukocyte antigen system-associated genes are significantly upregulated when PTX3 is lacking in esophageal carcinoma (ESCA).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue regarding uptake rates is the predominant focus on evidence from developed nations. There is limited evidence from developing countries, where the guidelines for HBOC risk management, prophylactic strategies, genetic testing, and counselling are lacking [ 54 ]. The extrapolation of uptake parameters from developed to developing countries could lead to an inaccurate estimation of the cost effectiveness of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the National Healthcare Security Administration of China developed the national reimbursement drug list, where medications are listed depending on their effectiveness and cost-effectiveness, and reimbursed entirely or partly by the public health insurance schemes 21. GDP per capita-based CETs are often used to determine whether a medication is cost-effective 22–32. This approach has been adopted in the China guidelines for pharmacoeconomic evaluations 33.…”
Section: Introductionmentioning
confidence: 99%